a) [TEX]A=(x+ \frac{3}{2})^2+1[/TEX].
Ta có [TEX](x+ \frac{3}{2})^2 \ge 0 \Rightarrow A \ge 1 [/TEX].
Vậy min A=1 khi [TEX]x+ \frac{3}{2}=0 \Rightarrow x= \frac{-3}{2}[/TEX].
b) [TEX]B= \left| x+ \frac{3}{4} \right|+ \frac{1}{5}[/TEX].
Ta có [TEX]\left| x+ \frac{3}{4} \right| \ge 0 \Rightarrow B \ge \frac{1}{5}[/TEX].
Vậy min [TEX]B= \frac{1}{5}[/TEX] khi [TEX]x+ \frac{3}{4}=0 \Rightarrow x= \frac{-3}{4}[/TEX].
c) [TEX]C=(x-3)^2+(y-1)^2+5[/TEX].
Ta có [TEX](x-3)^2,(y-1)^2 \ge 0 \Rightarrow C \ge 5[/TEX].
Vậy min C=5 khi [TEX]x=1,y=1[/TEX] .
d) [TEX]D=|x-3|+x^2+y^2+1[/TEX].
Hiển nhiên [TEX]y^2,x^2 \ge 0[/TEX].
Nên [TEX]D=|x-3|+x^2+y^2=|x-3+x^2|+y^2[/TEX].
Ta có [TEX]|x-3+x^2|=|x(x+1)-3|[/TEX].
Để D min thì [TEX]|x(x+1)-3|[/TEX] min, hay [TEX]|x(x+1)-3|=0[/TEX]
[TEX]\Rightarrow x(x+1)=3 \Rightarrow x = \frac{1}{2} ( \pm \sqrt{13}-1)[/TEX]
Vậy min D=1 khi [TEX]y=0, \ x = \frac{1}{2} ( \pm \sqrt{13}-1)[/TEX]